Studi Fenomenologis: Psychological Burden Remaja Laki-Laki dengan Ibu yang Mengalami Skizofrenia - Lifsha Zulvia; Yolivia Irna Aviani (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Adolescents living in families where a parent has schizophrenia are at risk of experiencing significant psychological distress. This study aims to gain an in-depth understanding of the subjective experiences of a teenage boy in dealing with the psychological burden of having a mother with schizophrenia. The research employed a qualitative approach with a phenomenological method and utilized Interpretative Phenomenological Analysis (IPA) for data analysis. The participant in this study was a 16-year-old male adolescent who lives with his mother diagnosed with a chronic mental illness. The findings reveal that the subject experienced psychological burden in both objective forms, such as caregiving duties and domestic responsibilities, and subjective forms, including feelings of shame, anxiety, limited social interaction, and emotional conflict. Despite these challenges, the subject developed adaptive coping strategies through social engagement, sports activities, and support from peers and the surrounding environment. These findings highlight the psychological dynamics faced by adolescents in families affected by mental disorders and emphasize the importance of experience-based approaches in psychological intervention efforts.